Altering the regioselectivity of T1 lipase from Geobacillus zalihae toward sn-3 acylglycerol using a rational design approach - Albayati, Samah Hashim; Masomian, Malihe; Ishak, Siti Nor Hasmah; Leow, Adam Thean Chor; Mohamad Ali, Mohd Shukuri; Mohd Shariff, Fairolniza; Muhd Noor, Noor Dina; Raja Abd Rahman, Raja Noor Zaliha (Multidisciplinary Digital Publishing Institute, 2023)
The regioselectivity characteristic of lipases facilitate a wide range of novel molecule unit constructions and fat modifications. Lipases can be categorized as sn-1,3, sn-2, and random regiospecific. Geobacillus zalihae T1 lipase catalyzes the hydrolysis of the sn-1,3 acylglycerol chain. The T1 lipase structural analysis shows that the oxyanion hole F16 and its lid domain undergo structural rearrangement upon activation. Site-directed mutagenesis was performed by substituting the lid domain residues (F180G and F181S) and the oxyanion hole residue (F16W) in order to study their effects on the structural changes and regioselectivity. The novel lipase mutant 3M switches the regioselectivity from sn-1,3 to only sn-3. The mutant 3M shifts the optimum pH to 10, alters selectivity toward p-nitrophenyl ester selectivity to C14-C18, and maintains a similar catalytic efficiency of 518.4 × 10−6 (s−1/mM). The secondary structure of 3M lipase comprises 15.8% and 26.3% of the α-helix and β-sheet, respectively, with a predicted melting temperature (Tm) value of 67.8 °C. The in silico analysis was conducted to reveal the structural changes caused by the F180G/F181S/F16W mutations in blocking the binding of the sn-1 acylglycerol chain and orientating the substrate to bond to the sn-3 acylglycerol, which resulted in switching the T1 lipase regioselectivity.